Ritualistic Nudity. Dressing and Undressing in Ovid’s Fasti - Di-Giusto, Tammy (ARYS. Antigüedad: Religiones y Sociedades, 2020)
Ovid’s Fasti is a work of significance in defining the relationship between religious identity and clothing. This article examines the interplay between dressing and the divine and considers the key role that dressing, undressing, and nakedness plays in the worship of certain deities in the Fasti. Clothing and nudity are intimately linked to the changing nature of the socio-political landscape in the worship of these deities. Contemporary rites in 1st cent. Rome relate to fertility, blur social boundaries, and recall ancient preliterate peoples prior to cultivation, providing historical continuity of cultic practices.